THE USE OF MICROALGAE Chlorella vulgaris FOR REDUCTION OF POLLUTANT LEVELS IN SEA WATER OF MUARA ANGKE POLLUTED BY DOMESTIC WASTE - Risma Tambunan; Aras Mulyadi; Dessy Yoswaty (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in April-June 2019, located at the Center for Environmental Technology Laboratory (PTL) - Agency for the Assessment and Application of Technology (BPPT), Geostech Building 820, Serpong Archipelago Puspitek, South Tangerang. The purpose of this study was to determine the growth of C. vulgaris microalgae cultured in Muara Angke seawater polluted by domestic waste and to analyze its ability to reduce pollutant levels based on chemical parameters from Muara Angke seawater polluted by domestic waste. The experimental design used was a Completely Randomized Design (CRD) with 3 treatments of different C. vulgaris concentrations consisting of 5% v / v, 15% v / v, and 25% v / v performed three times repetition and given control that was without the addition of C. vulgaris and observed physical parameters (Temperature) and chemical parameters (DO, pH, COD, Phosphate, Nitrate, and Ammonia). Data were analyzed statistically using Analysis Of Variance (ANOVA) and further tested using the LSD test to compare between treatments with a 95% confidence level. The results showed that algae C. vulgaris had the potential to reduce levels of pollutants in sea water polluted by domestic waste, and the best treatment in reducing levels of pollutants in sea water polluted by domestic waste was treatment C (25%) with the decrease in COD value of 75.76% , Phosphate at 80.72%, Nitrate at 91.76% and Ammonia at 76.17% so that the levels of pollutants in the media used are in accordance with quality standards for their designation.   Keyword: Chlorela vulgaris, domestic waste, COD, Phosphate, Nitrate, Ammonia